NLRP3 Is Involved in Neutrophil Mobilization in Experimental Periodontitis - Cheat, Banndith; Torrens, Coralie; Foda, Asmaa; Baroukh, Brigitte; Sadoine, Jeremy; Slimani, Lotfi; Witko-Sarsat, Véronique; Huck, Olivier; Gosset, Marjolaine; Bouchet, Jérôme (Frontiers in Immunology, 2022)
The NLRP3 inflammasome is overexpressed in gingiva of periodontitis patients but its role remains unclear. In our study, we use a periodontitis mouse model of ligature, impregnated or not with Porphyromonas gingivalis, in WT or NLRP3 KO mice. After 28 days of induction, ligature alone provoked exacerbated periodontal destruction in KO mice, compared to WT mice, with an increase in activated osteoclasts. No difference was observed at 14 days, suggesting that NLRP3 is involved in regulatory pathways that limit periodontitis. In contrast, in the presence of P. gingivalis, this protective effect of NLRP3 was not observed. Overexpression of NLRP3 in connective tissue of WT mice increased the local production of mature IL−1β, together with a dramatic mobilization of neutrophils, bipartitely distributed between the site of periodontitis induction and the alveolar bone crest. P. gingivalis enhanced the targeting of NLRP3-positive neutrophils to the alveolar bone crest, suggesting a role for this subpopulation in bone loss. Conversely, in NLRP3 KO mice, mature IL-1β expression was lower and almost no neutrophils were mobilized. Our study sheds new light on the role of NLRP3 in periodontitis by highlighting the ambiguous role of neutrophils, and P. gingivalis which affects NLRP3 functions.